EVALUATION OF SOME SELECTED MULBERRY GENOTYPES THROUGH BIOCHEMICAL ANALYSIS AND FEEDING TRIALS GROWN UNDER HILL CONDITIONS - MISRA, A. K.; DAS, B. K.; AHSAN, M. M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
An analysis on the quality and quantity of leaves produced from four temperate mulberry varieties e.g. M. indica (Local), B G59, Tr-10 and Kosen raised under hill conditions was made. Observations revealed that significant variations existed among the genotypes with respect to all biochemical constituents. Tr-10, a triploid variety though recorded highest protein, sugar and free amino acid, feeding trial did not correlate with the chemical constituents in the leaves. The leafarea, yield, moisture content was maximum in BC259, followed by Tr-10. Feeding trial with BC259, and Tr-10 involving P5 bivoltine strain indicated significant improvement in the economic characters of cocoons. The experimental results also revealed a clear picture between the ability of larvae to assimilate BC259, and Tr-10 more avidly over the local variety. Basing the overall performances of BC259, with espect to leaf productivity, optimum and balanced nutritional status and cocoon characters the variety could be adopted for large scale inroduction under hill areas in Darjeeling.